MALE PRODUCTION PATTERN IN STINGLESS BEE, TETRAGONULA NR. PAGDENI (HYMENOPTERA: APIDAE: MELIPONINI) IN INDIA - SHASHIDHAR VIRAKTAMATH; D. SHISHIRA (The Bioscan, 2020)
Male production pattern in stingless bee, Tetragonula nr. pagdeni was studied by trapping outgoing bees daily over a year (August 2017 to August 2018) in five colonies at Gandhi Krishi Vignana Kendra Campus of the University of Agricultural Sciences, Bengaluru for the first time in India. Males were produced throughout the year except two major breaks of 5- and 7-weeks during October and December-January in stronger colonies. However, in weaker colonies males occurred only during August, November, March, and June with intermittent long breaks. Stronger colonies produced more males (0 to 13 males/colony/week) than the weaker colonies (0 to 3 males/colony/week). Total number of males produced by stronger colonies ranged from 39 to 53 while in weaker colonies it ranged from 3 to 9 over a period of 52 weeks. At colony level, maximum of 13 male bees while at population level 22 male bees were produced in 36th standard week (September) of 2017. All the five colonies together produced 143 males during the study period. Based on these studies it is concluded that male production pattern in stronger colonies of stingless bee, Tetragonula nr. pagdeni is almost continuous and similar trend may occur in other species of stingless bees in India.